1997
DOI: 10.1074/jbc.272.33.20395
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Binding Domain from the α3 Chain of Type IV Collagen Inhibits Proliferation of Melanoma Cells

Abstract: Our previous studies have shown that a peptide corresponding to the residue sequence 185-203 of the NC1 domain of the ␣3 chain of basement membrane collagen (type IV) inhibits the activation of polymorphonuclear leukocytes. Peptides from the same region of the ␣1, ␣2, ␣4, and ␣5(IV) chains did not exhibit this property. Because of the intimate relationship between metastasizing neoplastic cells and vascular as well as epithelial basement membranes, we measured the cell adhesionpromoting activity of peptides fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 23 publications
2
73
0
1
Order By: Relevance
“…Integrins might also play a role in inducing the inhibitory e ect of collagen type IV. Collagen type IV was shown to inhibit proliferation of melanoma cells (Han et al, 1997) and breast cancer cells (Shahan et al, 1999a) by up to 67%. This inhibition was attributed to the Serine-N-Serine sequence of the a3(IV) collagen chain.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins might also play a role in inducing the inhibitory e ect of collagen type IV. Collagen type IV was shown to inhibit proliferation of melanoma cells (Han et al, 1997) and breast cancer cells (Shahan et al, 1999a) by up to 67%. This inhibition was attributed to the Serine-N-Serine sequence of the a3(IV) collagen chain.…”
Section: Discussionmentioning
confidence: 99%
“…These sites correspond to residues 56 -75 (designated peptide T3) and 185-203 of ␣3NC1 domain (17,18). Biological activity of both peptides was shown to be dependent on ␣ v ␤ 3 integrin binding.…”
Section: Contribution Of the Rgd And Non-rgd Motifs For Binding Ofmentioning
confidence: 99%
“…Instead, they identified a non-RGD region comprising residues 54 -132 of the ␣3NC1 domain that bound the ␣ v ␤ 3 integrin, which was later narrowed down to 25 residues using deletion mutagenesis and synthetic peptides (17). Another non-RGD region of the ␣3NC1 domain, residues 185-203, identified by Han et al (18) was demonstrated to inhibit proliferation of melanoma cells, and the receptor for this synthetic peptide was identified as ␣ v ␤ 3 integrin by affinity chromatography (19). Whether these two non-RGD motifs quantitatively account for the adhesive activity of the native RGD-␣3NC1 domain and its capacity to bind ␣ v ␤ 3 integrin has not been addressed.…”
mentioning
confidence: 99%
“…Recently, we directly identified α v β 3 and α v β 5 integrins as endothelial receptors for α3 NC1 domain by affinity chromatography and confirmed binding of purified integrins in vitro (Pedchenko et al, 2004). So far, specific integrin binding sites have been characterized only for α3 NC1 domain (Han et al, 1997;Maeshima et al, 2000a). One region was initially identified within the first half of α3 NC1 domain (residues 54-132), since corresponding recombinant protein inhibited proliferation of endothelial cells, induced apoptosis, and decreased tumor growth in nude mice (Maeshima et al, 2001a).…”
Section: Integrin Receptorsmentioning
confidence: 99%
“…This results in inhibition of the Cap-dependent protein synthesis mediated by focal adhesion/ phosphatidylinositol-3/Akt/mTOR kinases (Maeshima et al, 2002;Sudhakar et al, 2003). A second cell-binding site was ascribed to amino acids 185-203 of α3 NC1 domain based on the inhibition of melanoma cells proliferation by the corresponding synthetic peptide (Han et al, 1997). This peptide binds α v β 3 integrin and CD47/IAP from the cell lysate through specific interaction of β 3 subunit with amino acid triplet SNS (Pasco et al, 2000;Shahan et al, 1999).…”
Section: Integrin Receptorsmentioning
confidence: 99%